The Effect of Window Size Changing on Satellite Image Segmentation Using 2D Fast Otsu Method - Naji, T. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Multispectral remote sensing image segmentation can be achieved using a multithresholding technique. This paper studies the effect of changing the window size of the two dimensional (2D) fast Otsu algorithm that presented by Zhang. From the results, it shown that this method behaves as a search machine for the valleys (an automatic threshold), between the gray levels of the histogram with changing the size of slide window.  Keywords Image Segmentation, (2D) Fast Otsu method, Multithresholding, Automatic thresholding, (2D) histogram image.